Failed induction of labor (IOL): an overview regarding obstetric outcome and its significance in a health resource poor setting over a period of 11 months - Bassetty, Karthik Chandra; Ahmed, Reena Dutta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of the study was to evaluate the indications and outcomes of failed induction in primigravidae in a tertiary care hospital located in a health resource poor setting. Methods: We conducted a retrospective cross-sectional study on women admitted in the labor room and planned for induction of labor in Assam Medical College and Hospital, Dibrugarh from 1st July 2016 to 31st May 2017. Induction was considered successful if the patient delivered vaginally and failed if it ended up in Caesarean section. Results: A total of 201 primigravida patients were selected for the study of which 135 patients delivered by CS and 66 patients by spontaneous vaginal delivery. The average induction-delivery interval was found to be 18.9 hours. Average weight of the babies was 2.9 kg. The following factors are associated with increased rates of failed induction: Bishop’s score less than 5, Gestational age >41 weeks, teenage and elderly primi, oligohydramnios, prelabour rupture of membranes (PROM), hypertensive disorders of pregnancy, induction-delivery interval greater than 24 hours, absence of a dating ultrasound done in 1st trimester, meconium stained liquor, SGA and macrosomia babies. There has been a single maternal death due to rupture of uterus. Conclusions: Most common indication of doing IOL is post-dated pregnancy (>40 weeks of gestation). Majority of women (66%) had no dating ultrasound with them hence they were induced based on last menstrual period which is unreliable in most women leading to failed IOL.IOL protocol i.e. when to repeat and how long to wait was purely the duty consultant’s opinion in our study rather than following a protocol. IOL is an important obstetric procedure hence there is a dire need to develop a protocol for the same in our setup.